Komunikasi Politik Megawati Soekarnoputri Terhadap Kepemimpinan Jokowi dalam Pemberitaan Metro TV - Usep Saeful Kamal; Sadri Sadri (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2023)
Political communication is communication directed at achieving an influence in such a way that the problems discussed by this type of communication activity can bind all its citizens through sanctions jointly determined by political institutions. So that in political communication a political communication channel is needed which is a means or tool to facilitate the exchange of information or messages. The delivery of communication from communicators to communicants can be in the form of images, writing or actions. Meanwhile, television is a tool and structure that conducts political communication in the context of mass media as a means of making it easier to convey political messages. Metro TV's coverage as a public channel was allegedly utilized by Megawati Soekarnoputri in overseeing Jokowi's leadership from serving as Mayor of Solo to the second term President, 2019-2024. The purpose of this research is to obtain in-depth information and answers related to the impact of Megawati Soekarnoputri's political communication on Jokowi's leadership in Metro TV coverage.